Conceptual Design of a Modular Floating Multi-Purpose Island - Drummen, Ingo; Olbert, Gerrit (Frontiers in Marine Science, 2021)
The design of a modular floating multi-purpose island inherently involves interaction within a group with a large range of backgrounds such as engineering, architecture, sociology, climate modelling and more. A heuristic design approach was adopted for future island developers to make a first conceptual design. Four major design considerations were distinguished to discretize the design space: module size, module shape, module principle and module connection and mooring. For each consideration a set of evaluation criteria were defined. This paper describes the heuristic conceptual design procedure that was applied to the design of a modular floating island for offshore energy, offshore accommodation, aquafarming and offshore transport and logistics. Two reference installation scenarios with a different respective focus of functionality, located in the North Sea and in the Mediterranean Sea, were created as a basis for the design. The first step of the design procedure consisted of a participatory process involving stakeholders and experts to rate design options for each category of design considerations based on the evaluation criteria and with regard to the installation scenario. As a result, all design configurations could be associated with an overall rating. In a second step, the most favourable designs identified during the participatory design procedure were investigated numerically to assess force distribution throughout the island when exposed to wave and current loads. The numerical results indicate that contrary to initial estimates during Phase 1, wave forces on an island consisting of quadrangular modules do not significantly exceed those experienced by triangular base shapes. As quadrangular modules can be shown to provide a higher Ground-Space-Index, this gives them a distinct advantage. As a result of the design process for this application, a barge-like, square structure with a base size of 45m was chosen as the base module.